Tear film osmolarity variation between weeks in healthy and dry eye disease subjects - Pena-Verdeal, Hugo; Garcia-Queiruga, Jacobo; Sabucedo-Villamarin, Belen; Giraldez, María J.; Yebra-Pimentel, Eva (Arquivos brasileiros de oftalmologia, 2023)
ABSTRACT Purpose: The possible variability in diagnostic test results is a statistical feature of dry eye disease patients. The clinician should consider tear film variations over time since the timing of tear film measurements is important for proper diagnosis. The purpose of the present study was to analyze the inter-week variation of osmolarity measurement in healthy and dry eye disease participants. Methods: Based on the Dry Eye Workshop II (DEWS-II) diagnostic methodology report criteria, a battery of tests (Ocular Surface Disease Index [OSDI] questionnaire, breakup time, and corneal staining) was administered to rule out the presence of dry eye disease. A total of 40 qualified volunteers were recruited into two groups: with only 20 healthy and 20 dry eye disease participants. The inter-week variation of osmolarity in the two groups was measured using a TearLab osmometer in two sessions one-week apart. The differences between the results were calculated. Results: There were no significant differences in osmolarity between the two sessions for either the healthy (paired t-test; p=0.085) or dry eye disease (paired t-test; p=0.093) participants. Moreover, there was no significant correlation between the means and differences in either session on healthy (Pearson correlation: r=0.020; p=0.935) or dry eye disease (Pearson correlation: r=-0.022; p=0.928) participants. In session 1, there was a significant difference in osmolarity values between groups (unpaired t-test; p=0.001), but no difference was found in session 2 (unpaired t-test; p=0.292). Conclusions: The present study discovered no inter-week variation in the tear film osmolarity of healthy and dry eye disease participants classified based on the DEWS-II criteria.